2012
DOI: 10.1186/1471-2091-13-5
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic view on the developmental transfer of homologous 30 kDa lipoproteins from peripheral fat body to perivisceral fat body via hemolymph in silkworm, Bombyx mori

Abstract: BackgroundA group of abundant proteins of ~30 kDa is synthesized in silkworm larval peripheral fat body (PPFB) tissues and transported into the open circulatory system (hemolymph) in a time-depended fashion to be eventually stored as granules in the pupal perivisceral fat body (PVFB) tissues for adult development during the non-feeding stage. These proteins have been shown to act anti-apoptotic besides being assigned roles in embryogenesis and defense. However, detailed protein structural information for indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…The changes in the total proteome upon infection were quite striking. Several of the normally highly abundant proteins such as the 30 kDa lipoproteins [29] seemed drastically lowered in concentration, if not removed, from the proteome, possibly due to proteolytical degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in the total proteome upon infection were quite striking. Several of the normally highly abundant proteins such as the 30 kDa lipoproteins [29] seemed drastically lowered in concentration, if not removed, from the proteome, possibly due to proteolytical degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Unless otherwise noted, sample collection and experiments (gel electrophoresis, Western blotting, lipoprotein staining of native gel) were performed as described earlier [29]. The monoclonal antibody against Vg of Pteromalus puparum was a generous gift from Prof. Gong-Yin Ye; State Key Laboratory of Rice Biology, Institute of Insect Sciences, College of Agricultural and Biotechnology, Zhejiang University, China.…”
Section: Methodsmentioning
confidence: 99%
“…Most likely, all ten 30-kDa lipoprotein genes have a common ancestor that underwent differentiation and divergent evolution [12]. Moreover, differences in amino acid sequences are also observed between 30-kDa proteins from different silkworm strains [13]. Also, analysis of expressed sequence tags (ESTs) derived from several silkworm tissues indicated that the level of expression of the 30-kDa proteins varies.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are often called larval serum protein, larval specific serum proteins or larval haemolymph proteins. Comparative proteomics suggested that abundantly synthesized 30 K proteins in haemolymph of the fifth larval instar (the vigorous feeding stage) were taken up by and stored in fat body (storage tissue), to meet nutrient requirement of non-feeding stages, pupae, adults and eggs (Pakkianathan et al, 2012;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%